Pengembangan Buku Ajar Berbasis Cerita Bergambar Terhadap Pembelajaran Nahwu di Kelas XII Madrasah Aliyah Nurul Hidayah – Bojonegara - Yuliyanti Yuliyanti; Yuyun Rohmatul Uyuni (Saintifika Islamica, 2023)
The development carried out by the researcher is to develop the textbook on the basis of illustrated stories in the teaching of grammar, that is, on the topic of market, health, travel and tourism. The results of the textbook can be downloaded so that students can use it to learn the Arabic language. In production design using textbook development, the researcher made the book containing an explanation of the special material in this book. In order to validate the production, the researcher conducted an investigation of the product by means of the authenticator, that is, Muhammad Muizzudin, the master and Hayumi. In the production experiment, the first field test was conducted by the researcher for the pre-test and the post-test. Based on the previous introduction, the researcher presented the research questions as follows: 1) What are the specifications of the Grammar book for the second grade at Nurul Hidayah Islamic Secondary School in Bojonegara?  2) How is the development of the second-grade grammar teaching book at Nurul Hidayah Islamic Secondary School Bojonegara?  3) What is the effectiveness of the textbook in teaching grammar in second grade at Nurul Hidayah Islamic Secondary School Bojonegara? To know the effectiveness of developing the textbook for teaching grammar in the second grade at Nurul Hidayah Islamic Secondary School Bojonegara, we can see the results of the pre-test and the post-test. On the basis of data tables 5 and 6, it shows that the average value of the pre-test is 69.15 and the value of the post-test is 74.25. This indicates that the value of the post-test is better than the value of the pre-test. Therefore, the range between the pretest and posttest is 5.1%.